University Students’ Expectations of their Lecturers’ Support Regarding Extensive Reading – A Case Study of first-year English major students at a South African University - Madoda Cekiso; Florence Olifant (E-Journal of Humanities, Arts and Social Sciences)
Despite the importance of extensive reading in higher education, limited research has explored university students’ expectations of their lecturers’ support in this area. This qualitative case study investigated the expectations of 65 first-year English Majors students at a South African university regarding their lecturers’ support for extensive reading. The respondents were purposively selected and open-ended questionnaires were used to collect data, which was analyzed thematically. The findings revealed that students expected lecturers to provide guidance on digital reading, encourage reading groups, improve access to diverse reading materials, consider students’ reading interests, expose them to newspapers and magazines, and promote the use of social networks for extensive reading. The study highlights the importance of considering students’ perspectives in shaping reading instruction pedagogy and offers practical implications for lecturers to effectively support and facilitate extensive reading.